PRINSIP-PRINSIP EKONOMI ALQURAN - Ruslan, Ruslan (At-Taradhi, 2012)
This article uses historical, philosopical and legal approaches. It is historical for it traceseconomic activities back to the time of prophet Adam until prophet Muhammad. It is at the sametime, philosopical and legal in nature because there are discussions on some Qurâanic precepts oneconomy that need to be obliged. The four principles of âQurâanic economyâ are tauhid, balance,free will and responsibility. Starting from tauhid, a Muslim believes that his prayers and devotions,his life and death are only for Godâs sake. With balance, it is expected that no inflation, economicrecession and depression occur. With free will and responsibility, economic actors are expected towork hard and execute Godâs mandates.